Philosophy in the Nature of Science - Farhan Hidayat; Usiono, Usiono (al-Afkar, Journal For Islamic Studies, 2025)
The notions of philosophy, science and philosophy of science will be clarified through this study. This work is a qualitative research that aims to create meaning through selected literature. Dimensions Philosophy comes from everything that exists and might exist. A thorough understanding of the philosophy of science requires an etymological and terminological understanding of philosophy and science itself. Derived from the Arabic word “alima” which means knowledge, science is terminologically precise and structured knowledge. Philosophy has its etymology in the Greek term philoshopia, which means love of knowledge. Philosophers' own definitions give many meanings to philosophical terms. Philosophy was defined by Aristotle as knowledge that incorporates truth and covers the fields of metaphysics, logic, rhetoric, ethics, and aesthetics. Thus, one can read philosophy of science as a philosophy that contains exact and structured truths about knowing. The tangible result of scientific philosophy is science. Its scope includes the axiological foundation, which is the virtue of science, the epistemological foundation, which is how knowledge is obtained, and the ontological foundation, which is what science really means.